2008
DOI: 10.1002/art.23961
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in systemic lupus erythematosus: Bone marrow analysis differentiates active from inactive disease and reveals apoptosis and granulopoiesis signatures

Abstract: Objective. The cells of the immune system originate from the bone marrow, where many of them also mature. This study was undertaken to examine gene expression in the bone marrow of patients with systemic lupus erythematosus (SLE), in order to better understand the aberrant immune response in this disease.Methods. Bone marrow mononuclear cells (BMMCs) from 20 SLE patients (11 with active disease and 9 with inactive disease) and peripheral blood mononuclear cells (PBMCs) from 27 patients (16 with active disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 54 publications
5
61
0
Order By: Relevance
“…Chemokines: Among the genes that were over-expressed in the peripheral blood relative to the bone marrow of SLE patients, Nakou et al [60] identified a number of chemokines, including CCR5, CXCL3L1, CXCL2 and CXCL3 and other interferon-responsive genes including IL6R. Similarly, Fu et al [61] and Bauer et al [62] also identified chemokines and cytokines whose gene expression was different in SLE than in healthy controls.…”
Section: Other Markersmentioning
confidence: 99%
“…Chemokines: Among the genes that were over-expressed in the peripheral blood relative to the bone marrow of SLE patients, Nakou et al [60] identified a number of chemokines, including CCR5, CXCL3L1, CXCL2 and CXCL3 and other interferon-responsive genes including IL6R. Similarly, Fu et al [61] and Bauer et al [62] also identified chemokines and cytokines whose gene expression was different in SLE than in healthy controls.…”
Section: Other Markersmentioning
confidence: 99%
“…In bone marrow mononuclear cells (BMMCs) of SLE patients, CCR5 and CX3CR1 expressions were downregulated as compared to those of healthy individuals. However, expressions of CCR5, CXCL3L1, CXCL2 and CXCL3 were upregulated in peripheral blood mononuclear cells (PBMCs) as compared to BMMCs in SLE patients [31]. These genes are associated with chemotaxis properties and migration of leukocytes.…”
Section: Other Cytokine and Chemokine Signatures In Slementioning
confidence: 99%
“…Rus et al [30] identified genes upregulated in active SLE included TNF family molecules (TNF-a converting enzyme; TACE and TNF RII); protease family (TIMP-3 and TIMP-4); neurotrophic factors family (NT-4 and NT-3); IL-17 and IL-13Ra2; and the co-stimulatory molecules (CD40 and CD27), while P-and R-cadherin genes from the adhesion molecule family were downregulated in PBMCs of active patients. Bone marrow cells of active SLE patients displayed apoptotic and granulopoiesis gene signatures [31]. SandrinGarcia et al [34] demonstrated uniquely expressed genes in active SLE patients and in SLE with remission.…”
Section: Other Cytokine and Chemokine Signatures In Slementioning
confidence: 99%
“…Despite chronic neutropenia and hyper-susceptibility to bacterial infections [15][16][17], a significant proportion of SLE patients display elevated levels of immature neutrophils and a pronounced granulopoiesis gene expression signature in cells from both peripheral blood and bone marrow exudates [2,18,19]. In addition, neutrophils are known to infiltrate target organs such as the skin, kidney or vasculature in SLE patients [20][21][22], although the pathogenic nature of such infiltration remains unknown.…”
Section: Pro-inflammatory Neutrophils In Accumulate In Sle Patients Amentioning
confidence: 99%